A Java Based Multimedia Distributed Computer Supported Collaborated World (CSCW) Environment Over the Internet - Kok, Chee Boon; Mukerjee, Malay R.; Mohd Ali, Borhanuddin; Ramli, Abdul Rahman (Universiti Putra Malaysia Press, 2001)
Computer Supported Collaborative Work (CSCW) and distributed computing have been termed as the next paradigm of computing which allows users to interact and collaborate with each other seamlessly over the network. As a result, many collaborative distributed CSCW system have been proposed and developed. However, most of the system fall short in providing platform independent system that address many real-world needs of users working together in a CSCW system. In this paper, efforts have been focused on creating a Distributed Computer Supported Collaborative Work environment for efficient collaborative editing and interaction among the participating users over the internet that support asynchronous and synchronous collaboration. Java has been used developed language.